The Standard of Selecting Friends and Its Effect on Friendship Quality among College students - HOU, Yongmei; Jiaxin, Kuang (Advances in Social Sciences Research Journal, 2021)
Objective To explore the present status of standard of selecting friends and friendship quality, and analyze the effect of standard of selecting friends on friendship quality among undergraduates. Methods A random sampling was used to select 1002 undergraduates through Internet in Guangdong province. They were investigated with Standard of Selecting Friend Scale for College Students (SSFS) and McGill Friendship Questionnaire (MFQ). Results ⑴ The friendship quality of undergraduates was relatively high, with MFQ total score of (254.16±38.80). ⑵ The most important standards of selecting friends were mutual compatibility and complementarity, followed by personality, physiology condition, social conditions and other conditions. ⑶ Multivariable stepwise linear regression showed that the total score of MFQ was positively correlated with the following 4 factors such as mutual compatibility and complementarity, personality, as well as other conditions (β=.477～.690，all P<.001). Conclusion The overall level of friendship quality among undergraduates is relatively high. Mutual characteristics may be related factors of friendship quality.